2019
DOI: 10.1103/physrevb.99.155423
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic modes and resonances of two-dimensional bodies

Abstract: The electromagnetic modes and the resonances of homogeneous, finite size, two-dimensional bodies are examined in the frequency domain by a rigorous full wave approach based on an integro-differential formulation of the electromagnetic scattering problem. Using a modal expansion for the current density that disentangles the geometric and material properties of the body the integro-differential equation for the induced surface (free or polarization) current density field is solved. The current modes and the corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The transverse (magnetostatic) modes of the particle are solution of the eigenvalue problem [22], [23] V…”
Section: Longitudinal and Transverse Modes Of The Particlementioning
confidence: 99%
“…The transverse (magnetostatic) modes of the particle are solution of the eigenvalue problem [22], [23] V…”
Section: Longitudinal and Transverse Modes Of The Particlementioning
confidence: 99%
“…All these nomenclatures are equivalent. It was shown that this two sets of modes, even if this distinction is made in the long-wavelength regime, remain well distinguishable and have different properties even in the full-wave regime 23,27,28 .…”
Section: Electromagnetic Modesmentioning
confidence: 99%
“…where both the set of modes {u h (r)} and {v h (r)} are normalized, u * h , u h = 1 and v * h , v h = 1 for any h. This expansion is very useful because it separates the dependence on the material from the dependence on the geometry 23,24,27,45,46 , and has been used in different contexts 28,47,48 .…”
Section: Electromagnetic Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…2a with minor radius r, major radius R, with R = 2r, corresponding width w 0 = R − r = r, and a thickness h. To simplify our analysis, and only within the current subsection, we make the additional assumption that the ring has thickness h much smaller than R: under this hypothesis we can use the approximated method introduced in Ref. 41 to calculate the magnetoquasistatic modes of the ring, instead of the threedimensional but more computationally intensive method presented in. 22 The first seven modes exhibited by the ring resonator are shown in Figure 3a, which are are independent of h as long as h l c .…”
Section: Magnetoquasistatic Modesmentioning
confidence: 99%